Praktik Sosial Remarriage pada Masyarakat Minangkabau di Kenagarian Padang Ganting - Desmaisi Desmaisi; Jendrius Jendrius; Maihasni Maihasni (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2023)
: Remarriage is an individual who is married the same or more than twice by a man or a woman. Usually, marriage is done once in a lifetime. However, in Nagari Padang Ganting found men and women married many times. This study uses a qualitative method. Data was collected using in-depth interviews, observation and secondary data analysis. The practice of social remarriage (marriage again) in the Minangkabau community in Kenagarian Padang Ganting studied with structuration theory by Anthony Giddens is known that there are structures that enable or empower